Understanding Combustion - H S Mukunda (Hyderabad, 2013)
The phenomenon of combustion, seemingly so simple and present almost in all spheres of our lives, is a fascinatingly complex process that involves elements of chemistry, thermodynamics, and fluid mechanics. In Understanding Combustion, the author takes on the task of revealing its myriad aspects for the benefit of a general reader with a background in science.
English
Keywords: Engineering; Technology